Critical Parameter Analysis of Public WiFi Network Service Quality in Karanganyar Using TIPHON Standards - Nurul Kholisatul Ulya; Yuli Siyamto; Setyo Nugroho (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to identify the critical Quality of Service (QoS) parameters that most affect the quality of public WiFi networks in Karanganyar Regency. The study aimed to evaluate throughput, delay, packet loss, and jitter based on the TIPHON standard. This evaluation helps determine which factors contribute most to service degradation in public WiFi networks. The study also sought to provide recommendations for improving the user experience in high-traffic areas such as Karanganyar Square. Materials and methods. This study used a descriptive quantitative approach. Data were collected by measuring four QoS parameters: throughput, delay, packet loss, and jitter. Measurements were conducted at four strategic public WiFi locations in Karanganyar Regency. The collected data were analyzed to determine the QoS index and identify which parameters most significantly affect network performance. The TIPHON standard was applied to categorize the quality of each parameter. Results. The results showed that the overall average QoS index was in the “good” category (index 3). However, two parameters were identified as dominant factors in quality degradation: low throughput and high jitter, both in the moderate category. These issues were most pronounced in locations with high user traffic, particularly Karanganyar Square. The findings indicate that although the network generally meets user expectations, certain conditions can significantly affect performance. Conclusions. Public WiFi in Karanganyar Regency generally provides good service, but low throughput and high jitter reduce performance in high-traffic areas. Recommendations for improvement include increasing bandwidth capacity and optimizing traffic management to reduce jitter. Implementing these measures can enhance user experience and ensure more reliable network performance.